Linguistic Diversity in Croatia: Historical and Contemporary Perspectives on Language Contact (and Conflict) in the Zadar and Varaždin Regions - Škifić, Sanja; Pavić Pintarić, Anita (Jezikoslovni zapiski, 2024)
This article deals with historical and contemporary language contact between Croatian on the one hand and Italian and German on the other in the Zadar and Varaždin regions. It focuses on language contact identifiable in the analysis of linguistic items related to space and occurrences in space. Because language contact frequently results in language conflict, it also considers the possibility of correlating the two phenomena based on a corpus analysis and from the perspective of three areas of interest: language, individual language user(s), and society. The findings suggest that there is a difference between coastal and continental language contact and conflict in manners of naming places, but also that the contemporary language conflict between the languages analyzed is not as prominent as it was in the past.